The Development Of The Cultural Heritage Site Of Huis Van Behauring As Heritage Tourism Destination In Bengkalis - Muhammad Ikrom; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bengkalis city is the center of Bengkalis District government. In the Dutch colonial era, Bengkalis had become the residency of eastern Sumatra so that there were many colonial remains in the city. One of them is the Huis Van Behauring cultural heritage site which is a prison building that was once a place of exiled kings and leaders who opposed the Dutch government at that time. The research methods were field observations, literature reviews, and documentations. The development of the cultural heritage tourism and colonial architectural was emphasized on the area organization of the site and the appearance of buildings that showed the characteristics of colonial architectural buildings. The development location is on Jalan Pahlawan, Bengkalis with width 3,5 hectares. The concept used was taken from the title Bengkalis people give to Huis Van Behauring building, which is chain. The result of this study is the development of the Huis Van Behauring cultural heritage site used as a new historical tourist attraction in Bengkalis by applying the heritage tourism elements and the colonial architectural style. In addition, the development of this site is to preserve and revive the Huis Van Behauring site.Keywords: Colonial Architectural, Bengkalis, Heritage Tourism, Cultural Heritage, Huis Van Behauring,